From microcosm to macrocosm : individual households and cities in ancient egypt and nubia - Budka, Julia.; Auenmüller, Johannes.
As reflected in the title "From Microcosm to Macrocosm : Individual households and cities in Ancient Egypt and Nubia", both a micro-approach introducing microhistories of individual sites according to recent archaeological fieldwork incorporating interdisciplinary methods as well as general patterns and regional developments in Northeast Africa are discussed. This combination of research questions on the micro-level with the macro-level provides new Information about cities and households in Ancient Egypt and Nubia and makes the book unique. Architectural studies as well as analyses of material culture and the new application of microarchaeology, here especially of micromorphology and archaeometric applications, are presented as case studies from sites primarily dating to the New Kingdom (Second Millennium BC).